Pengaruh Level Rendaman Ekstrak Kulit Manggis (Garcia Mangostana L ) dan Daya Simpan terhadap Kualitas Fisik Telur Ayam Ras (Jurnal Riset Agribisnis dan Peternakan, 2022)
This study aims to determine the potential of mangosteen peel extract (Garcia Mangostana L) as an egg preservative to improve the physical quality of broiler eggs soaked for 6 weeks. This study used 105 chicken eggs, soaked for 24 hours and stored for 6 weeks. Methods Using Completely Randomized Design (CRD) with 4 treatments and 3 replications. The parameters taken are egg white index value, egg yolk index value, egg yolk color, pH value of egg white and yolk. The results showed that mangosteen peel extract had a significant effect (P
Keywords: Chicken eggs; Mangosteen peel; physical quality